2013
DOI: 10.1177/1740774512471452
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment strategy cost and impact on minority accrual to a breast cancer prevention trial

Abstract: Public transportation ads have the potential to generate numerous minority contacts and consents at a reasonable cost within an urban setting. Combined with traditional methods of recruitment, this method can lead to timelier study completion and increased minority accrual. Future research should prospectively track recruitment and costs in order to better assess the cost-effectiveness of recruitment methods used to target minority populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…This cohort of 127 black survivors of breast cancer is equal in size to the Women's Intervention Nutrition Study trial, which also included 127 black women . Our success in recruiting a diverse sample for the WISER Survivor Clinical Trial arises from lessons learned from previous studies regarding the efficient, effective recruitment of participants . The approaches outlined in the current study demonstrate that efficient, focused recruitment strategies can result in success in recruiting a diverse cohort of cancer survivors, even within the context of limited resources.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This cohort of 127 black survivors of breast cancer is equal in size to the Women's Intervention Nutrition Study trial, which also included 127 black women . Our success in recruiting a diverse sample for the WISER Survivor Clinical Trial arises from lessons learned from previous studies regarding the efficient, effective recruitment of participants . The approaches outlined in the current study demonstrate that efficient, focused recruitment strategies can result in success in recruiting a diverse cohort of cancer survivors, even within the context of limited resources.…”
Section: Discussionmentioning
confidence: 93%
“…Our hope was that this also would increase the rate of recruitment. We chose to pursue this, despite evidence that many of these additional outlets can be very costly, and yield very few participants …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies not only track this specialized recruitment success in real time but also assess the cost effectiveness of each modality employed so that they can more accurately target limited research dollars for maximal recruitment benefit. 53 Our own work in developing an observational longitudinal study on the influence of race and SES on the development of age-associated health disparities among middle aged residents of Baltimore outlines important barriers that are as relevant and applicable in observational clinical research as in cancer prevention research. 54 Three broad areas of barriers were identified that operate in close contiguity: individual-based barriers, community-based barriers, and researcher-based barriers.…”
Section: Cancer Prevention In At-risk Populationsmentioning
confidence: 99%
“…For example, a recent study interviewed Hispanics to create audiovisual materials in the form of a Spanish-language DVD and accompanying booklet [7]. Such strategies have been successful at increasing cancer clinical trial recruitment rates of minorities [1, 12]. …”
Section: Introductionmentioning
confidence: 99%